The Diversity of Edible Flowers and Its Biocultural Role in Local Food System in Dali, Southwest China - Qing Zhang; Jihai Zhang; Congli Xu; Xianjin Wu; Chunlin Long (Diversity)
Edible flowers (EFs) form a special group of food plants that serve a pivotal role in local food systems, both in their utilitarian value and cultural significance. Dali, renowned for its rich biocultural diversity, is home to various ethnic groups with unique traditions regarding the consumption of EFs. However, systematic and comprehensive ethnobotanical studies of EFs are lacking, and their biocultural significance has not been discussed. Through ethnobotanical surveys conducted in 15 markets across Dali, 163 taxa of EFs were documented, encompassing 56 families and 108 genera. They were consumed in 16 ways and as 5 types of food. Quantitative evaluations using the Relative Occurrence Frequency (ROF) and Cultural Food Significance Index (CFSI) assessed the local importance of these flowers. Comparisons were made with another site regarding flower-eating species and methods, revealing biocultural differences. The study highlights how these flowers contribute to local dietary practices and cultural traditions. The role of EFs in sustainable food systems (SFS) is discussed, with emphasis on their economic, environmental, and social impacts. Protecting biocultural diversity means maintaining reciprocal relationships between people and edible species, which are crucial nodes in local SFS.